SELF ESTEEM INFLUENCE ON EMOTIONAL INSTABILITY AMONG POSTGRADUATE MARRIED INDIVIDUAL IN KWARA STATE, NIGERIA - Abdulkareem, Habibat Bolanle; Yusuf, Jamila; Lasisi, Kamil Adekola (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
This study, a descriptive survey design, investigated the influence of self-esteem on emotional instability among married postgraduate students in Kwara State. The population comprises all full-time postgraduate students in Kwara State. The target population is married postgraduate students. The samples consist of 500 full-time postgraduates. The researcher selected 300 males and 200 females. Two hypotheses were formulated and tested in the study. Data were collected using the self-esteem scale and the Perth emotional scale to measure the level of emotional instability among married postgraduate students in Kwara State. The scales were adopted and have already been validated by the authors. The collected data were analyzed using frequency, mean, percentage, standard deviation, and t-test. It was revealed, among others, that there is a significant difference in emotional instability between male and female respondents. The result further shows that gender has a significant influence on the stability of married postgraduate emotions. The study also revealed that gender has no significant influence on the level of self-esteem among married postgraduate students in Kwara State. It was concluded that there is a gender influence on the emotional instability of married postgraduate students, but there is no gender influence on the level of their self-esteem. It was then recommended, among others, that strategies and activities that would build postgraduate students emotional stability be put in place to help them overcome the challenges.